Exploring the glucose-lowering and anti-inflammatory immune mechanism of artemether by AMPK/mTOR pathway and microbiome based on multi-omics - Jiang, Tao; Du, Peipei; Liu, Dongxia; Chen, Hetao; Ma, Yujin; Hu, Bin; Li, Jingna; Jiang, Hongwei; Li, Xuejiao (Frontiers in Pharmacology, 2025)
BackgroundDiabetes mellitus (DM) is a metabolic disease with high morbidity, which significantly affects human life and health expenditures. Previous studies have demonstrated that artemether (ATM) has anti-diabetes and anti-inflammation activities, but its mechanism has not been fully elucidated. This research aimed to elucidate the impact of ATM on glucolipid metabolism in a type 2 diabetes mellitus (T2DM) model db/db mice and what kind of role the gut microbiota played, and explored the underlying mechanisms involved.MethodsC57BL/KsJ-db/db mice were treated with 80 and 160 mg/kg of ATM for 8 weeks, with metformin as a positive control.ResultsATM treatment (160 mg/kg) observably ameliorated insulin resistance (IR), hyperglycemia, hyperlipemia and pathological injury in the liver and pancreas. In addition, ATM significantly decreased the expression of TNF-α, IL-1β, IL-6, NF-κB and IL-17A, and significantly increased the level of IL-10 in diabetic mice. 16S rRNA sequencing and targeted GC-MS metabolomics result indicated that ATM restored gut microbiota dysbiosis based on increasing beneficial bacteria Lactobacillus and reducing pathogenic bacteria Helicobacter and Prevotella leading to the accumulation of propionic and valeric acids and the reduction of lipopolysaccharides (LPS) release, intestinal inflammation and intestinal barrier damage. Network pharmacology and metabolomics identified the AMPK/mTOR pathway as the main signaling involved in ATM improves glucolipid metabolism and inflammation in T2DM. Western blotting results revealed that ATM suppressed the phosphorylation of mTOR, P38, P65, IKBα and IRS1 whlie increased the levels of p-AMPK, TLR4, and occludin in mice liver and colon.ConclusionTaken together, ATM may modulate the composition of gut microbiota, increasing the abundance of Lactobacillus, which in turn elevates the levels of SCFAs. The elevation of SCFAs, especially propionic acid, may activate the AMPK/mTOR pathway, leading to a decrease in the levels of TNF-α, IL-1β, IL-6, NF-κB, and IL-17A, while increasing the levels of IL-10, thereby alleviating the inflammatory state and improving glucolipid metabolic disorder in T2DM. These findings laid a theoretical foundation for the clinical application of ATM in T2DM.